Power management for internet of everything - Coustans, Mathieu; Dehollain, Catherine (River Publishers, 2018)
Addresses several advanced topics in the area of Power Management Analog and Mixed-Signal Circuits and Systems. The fundamental aspects of these topics are discussed, and state-of-the-art developments are presented. The book covers subject such as bio-sensors co-integration with nanotechnology. In this book, several advanced topics in the area of Power Management Analog and Mixed-Signal Circuits and Systems have been addressed. The fundamental aspects of these topics are discussed, and state-of-the-art developments are presented. The book covers subject areas like bio-sensors co-integration with nanotechnology, and for these CMOS circuits one popular application could be personalized medicine. Having seen the power assets for such technologies, and knowing what challenges these present for the circuits and systems designer, remote powering and sensors solutions are reviewed in the second chapter. The third chapter contains an industrial contribution on remote powering, presenting energy harvesting from the RF field to power a target wireless sensor network consumption. Having touched the idea of the low current consumption, aeA or Nano-Amp range and their transient behaviours are also described. Digital and large-scale integrated circuits - seen from an academic point of view - is included in chapter five, and this same topic from an industrial point of view is given in the chapter thereafter. An additional topic on the hall sensor, applied in an automotive case study, is then also presented. Approaching the duty-cycling of active mode, oscillator for timers and system-level power management including the cloud are covered in the last chapters. Power Management for Internet of Everything targets post-graduate students and those persons active in industry, whom understand and can connect system design with system on chip (SoC) and mixed-signal design as broader set of circuits and systems. The topic of Internet of Things (IoT), ranging from data converters for sensor interfaces to radios and software application, is also addressed from the viewpoint of power and energy management. The contents ensures a good balance between academia and industry, combined with a judicious selection of distinguished international authors.
Keywords: Internet of things.; Electric power.; Low voltage integrated circuits.; Electricity.; elektronické knihy; electronic books